Subcritical Water Extraction of Biological Materials. Issue 1 (2nd January 2017) - Gbashi, Sefater; Adebo, Oluwafemi Ayodeji; Piater, Lizelle; Madala, Ntakadzeni Edwin; Njobeh, Patrick Berka
Abstract : Extraction is a vital prerequisite in most scientific studies involving the isolation and analysis of compounds from biological/environmental systems. The use of large quantities of organic solvents in performing both conventional and modern methods of extraction of these substances stirs issues of safety, environmental concern and cost-effectiveness. Subcritical water extraction (SWE) offers a suitable, safe, cost-effective and environmentally safe alternative compared to other methods as it takes advantage of the special properties of supercritical water under high temperature and pressure conditions (100–374 °C, >50 bar) to extract non-polar analytes. This review presents a critical appraisal of the principles and dynamics of SWE, and the current applications as a viable tool in the extraction of compounds from various biological matrices. Although more research is needed to improve full SWE applications, its adoption in the extraction of phytochemicals as well as other bioactive molecules including mycotoxins from both plant and animal components seems promising and needs to be properly exploited.